Sameness, Persons, and the Resurrection: Debates between Locke, Stillingfleet, Holdsworth, and Trotter Cockburn - van der Bos, Anita (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2023)
According to Locke, scripture says nothing about the resurrection of the same body. We will be resurrected. But in what sense can resurrected Jane be the “same” as living Jane? Throughout his thinking, Locke holds that sameness of body and/or sameness of soul are not required for the resurrection of “the same Jane.” Sameness of person is required. Locke’s theory of personal identity was ground-breaking in the seventeenth and eighteenth centuries. It was provoking and resulted in a wave of critical responses. His distinction between “man” and “person” is important for his account of personal identity, but the distinction was hard for his contemporaries to understand. The correspondence between Locke and Edward Stillingfleet, for example, shows that for Stillingfleet the distinction between “man” and “person” is artificial. Having read this correspondence, Winch Holdsworth attacks Locke in a sermon in 1719 arguing that Locke denied the resurrection altogether. Catharine Trotter Cockburn tries to defend Locke in her Vindication. Despite her clear understanding of the distinctions applied by Locke, she too struggles with what to make of a person.